The Role of Norrie Disease Pseudoglioma (Ndp) in Cerebellar Development/Tumorigenesis and Its Relationship with the Sonic Hedgehog Pathway - Tokarew, Nicholas (Université d'Ottawa / University of Ottawa, 2017)
Medulloblastoma (MB), a cancer of the cerebellum, is the most common solid tumor affecting children. In the cerebellum, Sonic Hedgehog (Shh) drives the proliferative expansion of granule neuron progenitors (GNP). These cells are located in the external granule layer (EGL) and are the cells of origin of Shh-MB. We recently identified Norrie Disease Pseudoglioma (Ndp) as a novel downstream target of Hh signaling in the developing retina. Ndp encodes an X-linked cysteine-rich secreted protein called Norrin, which is best known for its role in angiogenesis and blood brain barrier (BBB) maintenance in the developing retina and cerebellum, respectively. Norrin mediates this effect by binding to its receptor Frizzled4 (Fzd4) and co-receptors LRP5/6 and Tpsan12 to activate the canonical, β-catenin-dependent Wnt signaling pathway in endothelial cells (ECs). We detected the expression of Ndp and all required receptors in mouse GNPs and MB samples. To investigate a potential role for Ndp in Hh-driven MB, we genetically and pharmacologically inactivated Ndp/Fzd4 signaling in Ptch+/- mice (a mouse model for human Gorlin syndrome), which dramatically increased the incidence and reduced the latency of MB. This accelerated rate of tumorigenesis was caused by an increase in the number of preneoplastic lesions (PNLs), the precursor lesions to MB, and a faster conversion of these lesions to MB. We showed that Ndp mediates this increase in tumorigenesis by signaling through endothelial cell receptor Fzd4 to alter the GNP stroma, which is characterised by 5 major alterations: 1) activated angiogenic program, 2) open BBB, 3) aberrant deposition of extracellular matrix, 4) aberrant lymphocyte recruitment and 5) reduction in meningeal lymphatic vasculature. We propose that these stromal alterations are associated with a pro-tumor microenvironment that promotes DNA damage in GNPs and leads to enhanced lesion formation and progression towards MB. This research highlights 1) an unanticipated role for Ndp/Fzd4 signaling in Shh-MB initiation and progression, 2) a role for stromal signaling in the regulation of MB development and 3) a previously undescribed role for Ndp signaling in maintaining meningeal cerebellum lymphatic vessels.
Keywords: Medulloblastoma; Stromal signaling; Sonic Hedgehog signaling; Wnt signaling